1999
DOI: 10.1172/jci4217
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin is a proinflammatory neuropeptide in colonic inflammation

Abstract: A growing body of evidence suggests that interaction of epithelial and immune cells via neuropeptides, hormones, and cytokines participate in the pathophysiology of diarrhea and intestinal inflammation (reviewed in ref. 1). Neurotensin (NT), a bioactive peptide (2) with a primary distribution in the brain and the gastrointestinal tract, has been localized by immunohistochemistry to endocrine cells (N cells) and neurons in the intestinal mucosa, submucosa, and muscularis of animals and humans (3). A wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
130
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 48 publications
1
130
0
5
Order By: Relevance
“…The highest levels of serum NT we had measured before were present in those children with ASD who had gastrointestinal symptoms (27). NT is also found in the gut (29,73) and increases permeability of the intestinal lumen (74). NT may enter the blood and reach the brain by stimulating perivascular mast cells (75,76), which disrupt both the gut-blood barrier (77,78) and the blood-brain barrier (BBB) (79)(80)(81) (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The highest levels of serum NT we had measured before were present in those children with ASD who had gastrointestinal symptoms (27). NT is also found in the gut (29,73) and increases permeability of the intestinal lumen (74). NT may enter the blood and reach the brain by stimulating perivascular mast cells (75,76), which disrupt both the gut-blood barrier (77,78) and the blood-brain barrier (BBB) (79)(80)(81) (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…These include other receptors known to participate in TxA-induced enteritis, such as the neurotensin receptor 1 and corticotrophin-releasing hormone receptors 1 and 2, both of which are up-regulated in response to TxA, and the CC chemokine receptor (CCR1). [49][50][51] In summary, our use of overlapping genetic and pharmacologic approaches showed that PAR 2 and its activators are proinflammatory in TxA-induced enteritis. Although each of these approaches by themselves has limitations, considered together our results show that deletion of PAR 2 and the proteases that activate this receptor protect against inflammatory responses to TxA.…”
Section: Contributions Of Proteases To C Difficile Txa-induced Enteritismentioning
confidence: 85%
“…Our previous studies on the role of additional neuropeptides such as substance P, neurotensin, and members of the corticotropinreleasing hormone (CRH) family of peptides in intestinal inflammation demonstrated that receptors for these molecules are expressed in intestinal epithelial cells and their expression is increased during the course of inflammation (30)(31)(32)(33)(34). Hence, to examine epithelial cell expression of MCH and its receptors, we used a laser capture microdissection (LCM) approach to isolate colonic epithelial cells from cryopreserved surgical specimens obtained from patients with IBD and controls (35).…”
Section: Mch Functional Receptors Are Expressed In Colonocytesmentioning
confidence: 99%